Synthesised Schiff Bases As A Potential Corrosion Inhibitor Of Aluminium. - Osman , Hasnah; Abd Hamid, S; Hussin, M H; L, P Yee; Rahim, A. Ab; Al-douh, M.; Yahya, S. (2008)

(untitled)
The use of inhibitors for the protection against corrosion in acidic media such as nitric acid, sulfuric acid and hydrochloric acid is widely reported. Schiff bases, a group of compounds containing nitrogen atoms were found to be efficient inhibitors for corrosion in acidic media. Some research work revealed that the inhibition efficiency of Schiff bases was found to be greater than their precursor, amines and aldehydes.